Evaluating Financial Reporting Quality: The Effects of Financial Expertise vs. Financial Literacy - McDaniel, Linda; Martin, Roger D.; Maines, Laureen A. (The Accounting Review, 2002)
Audit committees evaluate financial reporting quality as part of their corporate oversight responsibilities. Given this responsibility, the national stock exchanges now require all audit committee members to be financially literate and at least one member to have financial expertise. In light of recent debates over this requirement, we provide evidence on how experts and literates differ in their evaluations of financial reporting quality. Results suggest that experts' evaluations of financial reporting quality are more strongly associated with their assessments of characteristics underlying reporting quality (e.g., relevance) espoused in Statement of Financial Accounting Concepts No. 2's framework than literates' evaluations. Additionally, literates are more likely than experts to identify concerns about reporting treatments for business activities that are prominent in the business press or are distinguished by their nonrecurring nature, while experts are more likely to raise concerns about reporting treatments for less prominent, recurring activities. This same pattern occurs in the ratings of the quality of the reporting treatments for specific financial statement items with respect to elements underlying reporting quality (e.g., neutrality); literates (experts) assess the quality elements for the reporting treatments of prominent and nonrecurring items (less prominent and recurring items) comparatively lower than experts (literates). These results suggest that including financial experts on audit committees is likely to change the structure and focus of audit committee discussions about financial reporting quality, and may affect the committee's overall assessment of the quality of a company's financial reports.